Development and outdoor characterization of a hybrid bifacial HCPV module. (23rd January 2020) - Martínez, Juan F.; Steiner, Marc; Wiesenfarth, Maike; Fellmeth, Tobias; Dörsam, Tobias; Wiese, Martin; Glunz, Stefan W.; Dimroth, Frank
Abstract: Conversion of direct, diffuse, and albedo irradiance into electricity is demonstrated with a new kind of hybrid bifacial high‐concentration photovoltaic module named bifacial EyeCon. It consists of Fresnel lenses that concentrate the direct sunlight 321x onto III‐V triple‐junction solar cells that are mounted on the front surface of p‐PERC bifacial c‐Si cells. Thus, the Si absorbs the front and rear diffuse irradiance. Because III‐V and Si cells are electrically isolated (hence a 4‐terminal device) but thermally coupled by a dielectric adhesive, Si also acts as a heat distributing substrate. To accommodate the concentrator cells, we adapted the metallization layout and also optimized it for low intensity, ie, 200 W/m 2 on the front and 100 W/m 2 on the rear, using finite element network simulation. Additionally, when the concentrator cells are mounted on a bifacial Si cell instead of a metal heat distributor, their operating temperature is 16 K higher. However, we demonstrate with outdoor measurements that the power output of the bifacial EyeCon module reaches up to 326 W/m 2 when the direct to global irradiance ratio is 92%. At a lower fraction of 70% the bifacial Si cells augment the power output of the III‐V string by 19%rel Abstract : A new hybrid bifacial high‐concentration photovoltaic module capable of converting the direct, diffuse, and albedo irradiance into electricity is introduced. The module, named EyeCon, uses commercially available III‐V 3J and p‐PERC bifacial c‐Si solar cells. It was demonstrated that the highest power output (326 W/m 2 ) exceeded the performance of standard CPV by 7.6%rel when the proportion of direct light was 92%. When the direct component dropped to 70%, the improvement increased to 19%rel .